Performance of Centropomus parallelus fingerlings fed a diet supplemented with citrate and acetate - Bruno Corrêa da SILVA; Scheila DUTRA-MOURIÑO; José Luiz P. MOURIÑO; Cristina CARVALHO; Vinicius Ronzani CERQUEIRA (Boletim do Instituto de Pesca)
This study aimed to evaluate the addition of sodium acetate and sodium citrate in the diets of fingerling fat snook (Centropomus parallelus), through growth performance and modification of the intestinal microbiota. In the experiment, 3,000 fat snook fingerlings were used, with an initial average weight of 0.57 Â± 0.10 g. The fish were stocked into 12 tanks (50 L) at a density of 5 fingerlings L-1 per tank distributed in three treatments with four replicates. The treatments were as follows: control group (without supplementation), one group supplemented with sodium acetate, and another group supplemented with sodium citrate. The diets supplemented with organic salts were sprayed with cod liver oil previously homogenized with 3% sodium acetate or sodium citrate. The fish supplemented with sodium acetate showed higher final weight, length, and yield, compared with the control group fish. The intestine of fingerling fat snook showed lower counts of total heterotrophic marine bacteria in the fish supplemented with acetate and citrate in relation to fish of the control group. Lower counts of sucrose non-fermenting vibrios were also observed in fish supplemented with acetate. Through this study, it was possible to evaluate for the first time the dietary inclusion of organic salts in the diets of marine fish in Brazil, with the dietary inclusion of 3% sodium acetate showing benefits for performance of fingerling fat snook.